Determinants of BPR Competitiveness in New Normal Era: Empirical Study in Indonesia - Sipahutar, Ida Rumondang; Sari, Evita; Warman, Azizah Surayya (Otoritas Jasa Keuangan, 2023)
As the rural bank in Indonesia, Bank Perkreditan Rakyat (BPR) serves people with limited products and services and is less regulated compared to Commercial Banks. During the COVID-19 pandemic, the growth rate of BPR slowed down. We developed a hypothesis on the negative influence of financial technology (fintech) on the competitiveness and performance of BPR. Using all BPR companies and 22 Fintech Lending companies as samples to measure the HHI and Lerner Index, we found that BPR and Fintech Lending companies were competing in an unconcentrated market. Several variables could not be examined while studying the determinants of BPR’s competitiveness, including Regional GDP, BOPO, third party funds, Loan Credit, ROE, NIM, and CAR. Several determinants, such as the NPL, Fintech Lending, and COVID-19 pandemic, were found to have significant negative impacts on the BPR’s competitiveness. Interestingly, BPR’s banking digitalization, as represented by its IT capability, was found to be not significant in this study.